Mental distress, quality of life and social support in recurrent ovarian cancer patients during active chemotherapy. (September 2017) - Wen, Qiang; Shao, Zhuyan; Zhang, Ping; Zhu, Tao; Li, Dan; Wang, Shihua
Abstract: Background: Anxiety and depression are common sources of mental distress experienced by ovarian cancer patients. The purpose of this study was to identify changes in levels of mental distress during active chemotherapy, to characterize the impact of these changes on quality of life (QOL), and to study the potential buffering effect of social support in recurrent ovarian cancer patients. Methods: Anxiety and depression were assessed at baseline and three months after initiation of active chemotherapy using hospital anxiety and depression scale (HADS). QOL was evaluated at the same time points using European Organization for Research and Treatment [EORCT] 30-item core quality of life questionnaire (QLQ-C30) and QLQ-OV28. Social support was evaluated by perceived social support scale (PSSS) at baseline. Results: Our results showed recurrent ovarian cancer patients had high rates of anxiety and depression. Levels of anxiety, but not depression, were significantly decreased following active chemotherapy. Notably, both anxiety and depression were significantly associated with poorer QOL on all functioning domains, global health and most symptom domains at both baseline and after chemotherapy. Social support was associated with improved mental state and several functioning and symptom domains of QOL. Conclusions: Our study reveals a high prevalence of mental distress and its profound detrimental impact on QOL in Chinese women with recurrent ovarian cancer. Social support is beneficial to alleviate mental distress and improve QOL.